Revitalisasi Taman Desa Pasinan Sebagai Upaya Peningkatan Kualitas Lingkungan dan Kehidupan Sosial Masyarakat - Rafida Febriana Widya Putri; Rizma Melina Oktabian Alifani; Khairunnisa Salsabila Putri Prameswari; M. Catur Rizky; Didit Darmawan; Jahroni Jahroni; Arif Rachman Putra; Samsul Arifin; Pratolo Saktiawan (Lembaga Pengembangan Kinerja Dosen, 2024)
Pasinan Village Park is one of the public spaces that has great potential as a means of recreation, social interaction, and environmental conservation. However, over time, this park has experienced a decline in quality both in terms of infrastructure and biodiversity. This study aims to examine the revitalization process of Pasinan Village Park which involves the active participation of the local community, and to measure its impact on environmental quality and the social life of residents. The research method used is a case study with a qualitative approach, involving field observations, interviews with related parties, and document analysis. The results of the study indicate that the revitalization of the park not only improves the physical condition of the park, but also increases the sense of community ownership of public space, strengthens social ties, and supports local environmental conservation..